CARE MANAGEMENT OF MAMBRUK (Goura Victoria) AT THE BIRD AND ORCHID PARK (TBTA) BIAK NUMFOR, PAPUA - Pattiselanno, Freddy; Waite, Aldo Firdaus; Sambodo, Priyo (Media Konservasi, 2023)
More than 700 species of avifauna found in New Guinea including Indonesia and Papua New Guinea. Bird and Orchid Park (TBTA) in Biak, an ex-situ conservation facility of Papuan endemic birds and captive breeding center where Crowned Pigeon birds are raised. A study on care management of Goura victoria (Mambruk) is conducted to support the Master Plan for the development of TBTA as one of the Regional Technical Implementation Units under the Forestry and Environment Papua Province Office. This study indicates that feed given to Mambruk birds approximately 2.21 Kg for five individuals in average, or ± 442 g/individual, fresh, cut in the form of squares/dice, with specific smell characteristic of fresh fruit in brightly colored. Food is given once every day, between 08:00 WIT and 09:00 WIT, following the starting working hour at the TBTA Biak. Drinking water is available ad libitum. The cages used for breeding Mambruk birds in TBTA Biak are permanent cages made of wire iron for roofs and walls. Two types of cages are available, group and individual cages with supporting facilities such as eating and drinking places, rooting sites, places to make nests, trees and tubs for bathing. Eating and drinking places are cleaned before use. The environment around the cage in TBTA is quite clean. The design of the cage is quite safe for birds. Cages are rarely cleaned and no quarantine/isolation cages are available. The facility is not supporting with veterinarians to control the bird’s health, and schedule for regular health care programs.